Sherlock Holmes contributions to research projects - Cifuentes-Medina, José Eriberto; Camargo-Silva, Aura Lucia (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The proper preparation of a research project requires the knowledge, techniques, variables, trends and strategies that allow students to take a broad view of theentire research process. Todayit is part of the studyand development of any discipline, so we have tried to enrich and strengthen the ResearchMethodology course for students of the Regency in Pharmacy Technology, Faculty of Schooling of UPTC, in order to provide the necessary tools with which a student can understand and be able to develop projects and research papers for training. We particularly want to emphasize the development of good research proposal as a degree option that contributes to the solution of problems of social character that requires the local, regional and national levels.